Early effects of a forest fire on the diversity of fungal communities in pine forests in Left-Bank Ukraine with special emphasis on mycorrhizal fungi - Davydenko, K. V.; Vysotska , N. Yu.; Yushchyk , V. S.; Markina , T. Yu. (Forestry and Forest Melioration, 2020)
Forest fires constitute widespread and potentially destructive disturbances in forest ecosystems, particularly negative impact on soil mycorrhizal fungi which are major players of the belowground plant. This study investigated the short-term effects of wildfire on fungal communities in Left-Bank Ukraine with special emphasis on mycorrhizal fungi. During the fourteen months after autumn wildfire, fruiting bodies found in the plots were identified, and their mycological richness, diversity and production in both burned and unburnt areas were measured. Total fungal diversity decreased in burned plots, where fungal richness and diversity of mycorrhizal species were significantly lower. Our results also confirmed the data on a rather destructive influence of post-fire forest management on fungal diversity. Only three mycorrhizal fungi associated with Pinus sylvestris L. were common to both sites while pyrophilic species were in close association with burned sites. 3 Figs., 1 Table, 31 Refs. Key words: mycorrhiza, pine plantation, post-fire erosion, wildfire.